Experimental and mathematical model for evaluation of LDL uptake by the isolated blood vessels - Čolić, Maja (Medicinski časopis, 2012)
The aim of this study was to present the experimental model which can be used to determine LDL transport into the blood vessel wall. We used isolated rabbit’s carotid arteries under physiologically relevant constant pressure and perfusion flow in conditions more similar to in vivo. First we used Rapid dual – isotope dilution method and obtained data have shown that the transport of LDL cannot be precisely determined in this way because it is in the range of standard error. Then we used Steady - state method and at higher pressure (140±10 mmHg) uptake (Us) was 3.52 ± 1.07% than at lower pressure (p